2020
DOI: 10.1186/s12870-020-02364-w
|View full text |Cite
|
Sign up to set email alerts
|

Origin-dependence of variation in seed morphology, mineral composition and germination percentage in Gynandropsis gynandra (L.) Briq. accessions from Africa and Asia

Abstract: Background: Spider plant [Gynandropsis gynandra (L.) Briq.], an economically promising African leafy vegetable, characterized for leaf yield components and nutritive quality, exhibits poor seed germination that hinders a wider expansion of the crop in urban and periurban horticultural systems. So far, there is little information pertaining to seed morphological traits and mineral elements content that may be associated with higher seed germination. This research investigated the hypothesis that spider plants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
(33 reference statements)
4
9
0
Order By: Relevance
“…Zharare (2012) observed differences in seed dormancy expression between the biotypes of G. gynandra. This was further confirmed by Blalogoe et al (2020) who found that Asian accessions exhibited small seeds with high germination. A possible way to solve the low germination in some accessions would be to select out the genes limiting that trait.…”
Section: Industrial Development Pathways and New Research Avenuessupporting
confidence: 58%
See 2 more Smart Citations
“…Zharare (2012) observed differences in seed dormancy expression between the biotypes of G. gynandra. This was further confirmed by Blalogoe et al (2020) who found that Asian accessions exhibited small seeds with high germination. A possible way to solve the low germination in some accessions would be to select out the genes limiting that trait.…”
Section: Industrial Development Pathways and New Research Avenuessupporting
confidence: 58%
“…Further studies integrating more diverse germplasm collections and the use of whole-genome sequences would be helpful to reconstruct the demographic history of the species in the lights of expansion of utilisations (e.g. industrial utilisation of health promoters, establishment of improved seed value chains, leaf processing for consumption) and new scientific endeavours (see Table 2) by Omondi et al (2017b), Sogbohossou et al (2020), andBlalogoe et al (2020).…”
Section: Origin Systematics and Geographical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies and reviews have shown that larger and heavier seeds germinate faster than smaller and lighter seeds (Ambika et al, 2014; Hojjat, 2011; Mandal et al, 2008; Springfield, 1973), although some few studies have noticed the opposite (Blalogoe et al, 2020; Xu et al, 2017). Indeed, it has been shown that besides germinating better, heavier seeds usually produce larger plants in height, and with a greater number of leaves, stem girth and dry weight (Nagaraju, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gynandropsis gynandra (L.) Briquet is a monoecious herb species in the family Cleomaceae. It is widely distributed in many subtropical and tropical regions of the world such as China, India and sub-Saharan Africa (Blalogoe et al 2020 ). As an important commercial crop, its leaves can provide us with vitamin A, vitamin C, flavonoids and essential minerals (calcium and iron) for medicinal uses.…”
mentioning
confidence: 99%